2022
DOI: 10.1084/jem.20220780
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 breakthrough infection in vaccinees induces virus-specific nasal-resident CD8+ and CD4+ T cells of broad specificity

Abstract: Rapid recognition of SARS-CoV-2–infected cells by resident T cells in the upper airway might provide an important layer of protection against COVID-19. Whether parenteral SARS-CoV-2 vaccination or infection induces nasal-resident T cells specific for distinct SARS-CoV-2 proteins is unknown. We isolated T cells from the nasal mucosa of COVID-19 vaccinees who either experienced SARS-CoV-2 infection after vaccination (n = 34) or not (n = 16) and analyzed their phenotype, SARS-CoV-2 specificity, function, and pers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 38 publications
5
63
0
Order By: Relevance
“…We did, however, detect SARS-CoV-2-specific T RM cells in the nasal mucosa of infected mice, as well as Mtb-specific T cells in the nasal mucosa of M. tuberculosis infected macaques. Moreover, it was also recently shown that virus-specific T cells can be detected in the nasal secretions of previously vaccinated humans who acquire breakthrough SARS-CoV-2 infections ( 55 ). Therefore, it is not clear why primary intranasal SARS-CoV-2 infection fails to induce a primary effector spike-specific T cell response in the nasal mucosa in rhesus macaques.…”
Section: Discussionmentioning
confidence: 99%
“…We did, however, detect SARS-CoV-2-specific T RM cells in the nasal mucosa of infected mice, as well as Mtb-specific T cells in the nasal mucosa of M. tuberculosis infected macaques. Moreover, it was also recently shown that virus-specific T cells can be detected in the nasal secretions of previously vaccinated humans who acquire breakthrough SARS-CoV-2 infections ( 55 ). Therefore, it is not clear why primary intranasal SARS-CoV-2 infection fails to induce a primary effector spike-specific T cell response in the nasal mucosa in rhesus macaques.…”
Section: Discussionmentioning
confidence: 99%
“…The large degree of overlap between expanded and scAIM-TCRseq-con rmed clonotypes indicates that comparison of serial blood TRB repertoires may be a suitable surrogate for resource-intensive AIM-or peptide-HLA oligomer-scTCRseq to assign TRB sequences as vaccine antigenspeci c. AIM-scTCRseq data from this report substantially augment databases 50 used to match to estimate T cell responses to vaccines, as reported for adenovirus-based SARS-CoV-2 products 51,52 . While limited data suggest that intramuscular mRNA vaccination alone can result in nasal S-speci c CD8 + T cells 11 , more research is required to assess the contribution of a priming or breakthrough infection 12 for the emplacement of SARS-Cov2-speci c T RM in the nose. Here we show that vaccine-expanded clonotypes in circulation are detectable in the nose in persons with hybrid immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest that in most persons, the recognition of multiple T cell epitopes 5,6 largely preserves T-cell responses despite VOC evolution 7 , although T cell escape has been observed in a minority of persons 8 . Animal models suggest that T cells found in the airway protect against respiratory coronavirus challenge 9,10 , and recent functional data in humans document tissue-resident memory S-speci c T cells after SARS-CoV-2 mRNA vaccination 11 or breakthrough infection 12 . These data motivated detailed studies of T cells in hybrid immunity.…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…A goal of vaccination is to induce the type of immune response that most closely approximates natural immune protection against infection, while eliminating risks of disease. For COVID-19, despite some controversy 56 , human vaccinees to parenteral SARS-CoV-2 do not appear to induce robust airway-resident antigen-specific T cells, unlike those who experienced natural infections 57,58 . This highlights the potential of next-generation COVID-19 vaccines to improve mucosal and systemic immune responses through modulation of T cells.…”
Section: Discussionmentioning
confidence: 99%